Why are girls still dying unnecessarily? The need to address gender inequity in child health in the post-2015 Development Agenda - John Jungpa Park; Luciana Brond (Edinburgh University Global Health Society, 2015)
There is need for better quality evidence on the role of gender in child health achievements both globally and regionally. Renewed efforts are needed to ensure that gender equity is achieved in child health globally. Efforts should be prioritized in countries with excess female child mortality.